FURTHER APPLICATION OF SCENARIO ANALYSIS WITHIN THE INCOME APPROACH TO APPRAISAL OF AN OIL COMPANY - Vanchukhina, Lubov; Leybert, Tatyana; Khalikova, Elvira; Rudneva, Yuliya (Revista Inclusiones, 2020)
The study is relevant because Russian companies invite foreign investors interested in growing cost of equity, while investment prospects depend on appropriate valuation of assets. The article aims to assess probable dynamics of a company’s shares under various scenarios proceeding from the analysis of production factors influencing its value in the Russian market. Accordingly, the study used the scenario approach to forecast the company performance indicators under the optimistic, pessimistic and baseline scenarios. The work suggests an income approach-based business appraisal method supplemented with the analysis of the optimistic, pessimistic and baseline business development scenarios. Also, the results of this method applied to the valuation of an oil company are provided. The figures taken from its financial accounts as of 2012-2016 and analysed, formed the basis of three 5-year cash flow and value forecasts according to the different scenarios.